The Role of Early Maladaptive Schemas, Resilience, and Coping Styles in Predicting Intolerance of Uncertainty among Female Nurses - Najafi Aliehkolaei, Mohammad; Malek Mohammadi , Nazgol; Momeni , Fatemeh; Abedi, Shaghayegh; Mostafavi , Elham; Zadhasan , Zohreh (Psychology of Woman Journal, 2026)
Objective: This study aimed to examine the predictive role of early maladaptive schemas, resilience, and coping styles in explaining intolerance of uncertainty among female nurses in Tehran.Methods and Materials: The research employed a correlational descriptive design. The study population consisted of female nurses working in hospitals across Tehran, from which 410 participants were selected using the Morgan and Krejcie sample size table. Data were collected using the Intolerance of Uncertainty Scale, the Young Schema Questionnaire–Short Form, the Connor–Davidson Resilience Scale, and the Coping Inventory for Stressful Situations. Data analysis was performed using SPSS version 27. Descriptive statistics were reported, Pearson correlations were conducted to examine bivariate relationships, and multivariate linear regression was used to identify predictors of intolerance of uncertainty. Assumptions of regression analysis were tested and confirmed.Findings: Results indicated that all schema domains were significantly and positively correlated with intolerance of uncertainty (r values ranging from .39 to .56, all p < .01). Resilience (r = –.48, p < .01) and task-oriented coping (r = –.44, p < .01) were negatively correlated with intolerance of uncertainty, whereas emotion-oriented coping (r = .41, p < .01) and avoidance-oriented coping (r = .37, p < .01) were positive correlates. The regression model was statistically significant, F(9, 400) = 78.62, p < .01, with R² = .41, indicating that the predictors explained 41% of the variance in intolerance of uncertainty. Overvigilance/inhibition (β = .23, p < .01) and disconnection/rejection (β = .19, p < .01) emerged as the strongest schema-related predictors, while resilience (β = –.31, p < .01) and task-oriented coping (β = –.22, p < .01) were protective factors.Conclusion: The findings demonstrate that maladaptive schemas and maladaptive coping styles increase intolerance of uncertainty, whereas resilience and task-oriented coping reduce it. These results underscore the need for schema-focused interventions, resilience-building programs, and coping-skills training to enhance psychological well-being among nurses.